2022
DOI: 10.1001/jamanetworkopen.2022.26265
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Model for Laparoscopic Colorectal Surgical Instrument Recognition Using Convolutional Neural Network–Based Instance Segmentation and Videos of Laparoscopic Procedures

Abstract: IMPORTANCEDeep learning-based automatic surgical instrument recognition is an indispensable technology for surgical research and development. However, pixel-level recognition with high accuracy is required to make it suitable for surgical automation. OBJECTIVE To develop a deep learning model that can simultaneously recognize 8 types of surgical instruments frequently used in laparoscopic colorectal operations and evaluate its recognition performance. DESIGN, SETTING, AND PARTICIPANTS This quality improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…With the improvement of MRI technology, biomedical images of patients have become clearer and more accurate, which has made it closely related to clinical diagnosis and treatment of tumors [ 5 , 6 ]. Although MRI images can be reconstructed into 3D images, they are currently mostly presented in 2D form, and there is still a gap between conventional flat displays and the 3D structures of the human body [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of MRI technology, biomedical images of patients have become clearer and more accurate, which has made it closely related to clinical diagnosis and treatment of tumors [ 5 , 6 ]. Although MRI images can be reconstructed into 3D images, they are currently mostly presented in 2D form, and there is still a gap between conventional flat displays and the 3D structures of the human body [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Image recognition has been successfully applied in real-time vascular anatomical image navigation [1], or for automatically measuring distance of anatomical landmarks or size of organs intraoperatively, for example bowel length [2]. In 2022, Kitaguchi et al also reported on development of a model for laparoscopic colorectal surgical instrument recognition system using convolutional neural network-based instance segmentation and videos [3]. Real-time surgical phase recognition has been presented in many papers, using neural network-based deep learning techniques [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…In essence, instance segmentation allows for the pixelwise classification of individual objects within a surgical field, whether they are anatomical structures or surgical instruments. Although, it is the most preferred recognition technique for intraoperative guidance ( 9 ), previous attempts have been limited to segmenting rigid surgical instruments ( 10 ), as opposed to anatomical structures, which are often characterised by semi-rigid boundaries and thus pose a more difficult segmentation task.…”
Section: Introductionmentioning
confidence: 99%
“…Although few, there have been some platforms and clinical evidence in general surgery that attests to the accuracy and the significance of AI software in an intraoperative setting ( 7 , 9 , 11 14 ). Neurosurgery, at the forefront of cutting-edge technology, has witnessed numerous advancements in AI applications; however, these applications are limited to surgical phase recognition ( 15 ), detection and surveillance ( 16 ), diagnosis ( 17 , 18 ), endovascular navigation ( 16 ), training and preoperative planning ( 2 , 16 , 19 21 ), intraoperative imaging, and workflow automation ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation